Serological markers of intestinal barrier impairment do not correlate with duration of diabetes and glycated hemoglobin in adult patients with type 1 and type 2 diabetes mellitus - Hoffmanová, I; Sánchez, D; Szczepanková, A; Hábová, V; Tlaskalová-Hogenová, H (Physiological research, 2022)
Growing evidence suggests that diabetes mellitus is associated with impairment of the intestinal barrier. However, it is not clear so far if the impairment of the intestinal barrier is a consequence of prolonged hyperglycemia or the consequence of external factors influencing the gut microbiota and intestinal mucosa integrity. Aim of the study was to perform an estimation of relationship between serological markers of impairment of the intestinal barrier: intestinal fatty acid-binding protein (I-FABP), cytokeratin 18 caspase-cleaved fragment (cCK-18), and soluble CD14 (sCD14) and markers of prolonged hyperglycemia, such as the duration of diabetes mellitus and glycated hemoglobin (HbA1c) via a correlation analysis in patients with diabetes mellitus. In 40 adult patients with type 1 diabetes mellitus and 30 adult patients with type 2 diabetes mellitus the estimation has been performed. Statistically significant positive correlation was found between cCK-18 and HbA1c (r=0.5047, p=0.0275) in patients with type 1 diabetes mellitus with fading insulitis (T1D). In patients with type 1 diabetes mellitus with ongoing insulitis (T1D/INS) and in patients with type 2 diabetes mellitus (T2D), no statistically significant positive correlations were found between serological markers of intestinal barrier impairment (I-FABP, cCK-18, sCD14) and duration of diabetes or levels of HbA1c. Similarly, in cumulative cohort of patients with T1D/INS and patients with T1D we revealed statistically positive correlation only between HbA1c and cCK-18 (r=0.3414, p=0.0311). Surprisingly, we found statistically significant negative correlation between the duration of diabetes mellitus and cCK-18 (r=-0.3050, p=0.0313) only in cumulative group of diabetic patients (T1D, T1D/INS, and T2D). Based on our results, we hypothesize that the actual condition of the intestinal barrier in diabetic patients is much more dependent on variable interactions between host genetic factors, gut microbiota, and environmental factors rather than effects of long-standing hyperglycemia (assessed by duration of diabetes mellitus or HbA1c).
Keywords: Glycated Hemoglobin A; Diabetes Mellitus, Type 2; Hyperglycemia; diabetes mellitus 1. typu; dospělí; lipopolysacharidové receptory; Adult; Humans; biologické markery; lidé; diabetes mellitus 2. typu; Biomarkers; glykovaný hemoglobin; Lipopolysaccharide Receptors; Diabetes Mellitus, Type 1; hyperglykemie; Glycated Hemoglobin